THE ROLE AND PROSPECTS OF ARTIFICIAL INTELLEGENCE TECHNOLOGIES IN FOREIGN LANGUAGE LEARNING - Ramazanov Khumoyiddin (“SUN’IY INTELLEKTNING TIL O‘RGANISHDAGI O‘RNI” MAVZUSIDA TALABALAR ILMIY-AMALIY KONFERENSIYASI, 2025)
This thesis explores the role, potential, and effectiveness of artificial intelligence technologies in the process of foreign language learning. Based on experimental results, it discusses the integration of AI tools into education, their advantages, limitations, and future prospects. The work presents new academic insights and practical recommendations on how AI is transforming language teaching methodology in the digital age.